Konstruksi Keindonesiaan Dalam Film Tjokroaminoto - Ahmad Toni (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2018)
ABSTRACT This study uses critical discourse analysis method that aims to reveal the meaning of Indonesian keynthones in Tjokroaminoto Guru Bangsa film. The results show that the representation of meaning at Indonesian level at the text level is a representation of the dominance of ethnic or racial tribes of Europe and Arabia and subordinan tribes or races of Javanese, Chinese, Sundanese and do not have citizenship. At the messo level the purpose of the film production system is the goal of Tjokroaminoto's historical reconstruction based on the spirit of Islam as the basis for the struggle. At the macro level shows the construction of national leadership is a rational effort in order to fulfill party politics based on the spirit of keindonesiaan. Keindonesiaan is the essence of the teachings of cultural Islam that upholds human values in order to realize the concept of hijra or civil society in Indonesia. Key Words: Representation of Meaning of Indonesianness, Film of Tjokroaminoto Guru BangsaABSTRAKPenelitian ini menggunakan metode analisis wacana kritis yang bertujuan untuk mengungkapkan konstruki makna keindonesiaan di dalam film Tjokroaminoto Guru Bangsa. Hasil penelitian menunjukkan bahwa representasi makna keindonesiaan pada level teks merupakan representasi dominasi suku atau ras Eropa dan Arab dan subordinan suku atau ras Jawa, Tionghoa, Sunda, dan tidak mempunyai kewarganegaraan. Pada level messo tujuan sistem produksi film merupakan tujuan rekonstruksi sejarah Tjokroaminoto yang didasari oleh semangat Islam sebagai dasar perjuangan. Pada level makro menunjukkan konstruksi kepemimpinan nasional merupakan usaha rasional dalam rangka pemenuhan politik kepartaian yang didasari semangat keindonesiaan. Keindonesiaan merupakan hakikat ajaran Islam Kultural yang menjunjung tinggi nilai kemanusiaan guna mewujudkan konsep hijrah atau masyarakat madani di Indonesia.Kata Kunci: Representasi Makna Keindonesiaan, Film Tjokroaminoto Guru Bangsa